THE MOST COMPACT SCISSION CONFIGURATION OF FRAGMENTS FROM LOW ENERGY FISSION OF 234U AND 236U - Rojas T., Justo A. (2009)
Using a time of flight technique, the maximal values of the kinetic energy as a function of the primary mass of fragments from low energy fission of 234U and 236U were measured by Signarbieux et al. From calculations of scission configurations, one can conclude that, for those two fissioning systems, the maximal values of the total kinetic energy corresponding to fragmentations (42Mo62, 50Sn80) and (42Mo64, 50Sn80) respectively, are equal to the available energy, and that their scission configurations are composed of a spherical heavy fragment and a prolate light fragment, both in their ground state.